RELATIONSHIP BETWEEN STEM VIDEOS IN TEACHING AND STUDENTS’ LEARNING ENGAGEMENT - Ismail, Mohd Zaid; Mansor, Azlin Norhaini; Iksan, Zanaton; Mamad, Norwani (PEOPLE: International Journal of Social Sciences, 2020)
The use of multimedia like a video is one of the most effective methods of teaching and learning especially for Science, Technology, Engineering and Mathematics (STEM) subjects. This study aimed to identify the relationship or impact of STEM video use on student learning engagement in Malaysia. A quantitative study using survey design was conducted on 367 teachers teaching STEM subjects in Malaysia. The study data were analyzed using SPSS 20 software and the findings indicate that the level of STEM video use among teachers is high (mean = 3.65, sd = 0.48). Student engagement levels were also high (mean = 3.63, sd = 0.45). The findings also show a positive relationship between STEM video use in teaching and learning and student learning engagement (r = 0.685. Sig. = 0.00).The study might have implications for teaching and learning process and the policymakers in framing future strategies in teaching STEM subjects. In conclusion, teaching using STEM video has an impact on student learning engagement.